Non-traditional component of metabolic syndrome in children with obesity: Assesment of TG:HDL-C ratio as insulin resistance component / Nur Zati Iwani Ahmad Kamil - Nur Zati Iwani, Ahmad Kamil (2021)
Paediatrics metabolic syndrome (MetS) is on the rise parallel to the increased prevalence of childhood obesity. Although insulin resistance (IR) is an important variable in the diagnosis of MetS, the existing paediatric definition of MetS only measures elevated fasting blood glucose (FBG). Arguably, many children with severe IR can still regulate their FBG, especially in children with obesity. Therefore, this study aims to assess the utility of triglyceride to high-density lipoprotein-cholesterol (TG: HDL-C) ratio as an IR marker in the modelling of paediatric MetS among children with obesity using structural equation modelling (SEM). This is a cross-sectional study in which the cross- sectional baseline data of children with obesity participated in the main MyBFF@school programme, a school-based, cluster randomised controlled trial (C-RCT) study were sub- analysed. A total of 524 children were selected from 1255 children with obesity (age 10 to 16 years old) who have completed their anthropometric measurements including waist circumference (WC). Both exploratory (EFA) and confirmatory factor analysis (CFA) were used to examine TG: HDL-C ratio as an IR marker in paediatric MetS. This study compares and evaluates two competing fourfactor models for each of the first and second order-construct that consists of four core components (obesity, lipids, IR, and blood pressure) of MetS with changed variables to the IR factor. Model 1 used FBG, homeostatic model assessment for insulin resistance index (HOMA-IR), and insulin as an IR factor whereas in Model 2, FBG is substituted with TG: HDL-C ratio. Additionally, one model was included (model 3) consisting of Leptin: Adiponectin ratio (LAR) which iv is an obesity-IR marker as a reference model. Majority of the children (≈60%) were found to be abdominally obese. The overall prevalence of MetS was 6.9% (n=36) although about 40% of the children had IR and ≈60% had acanthosis nigricans. This result highlighted the presence of cardiometabolic risk and a high prevalence of IR in children with obesity. The TG: HDL-C ratio (standardised factor loading = 0.904) group with HOMA-IR (standardised factor loading = 0.664) indicated a strong correlation to the IR factor. Additionally, all MetS factor structures showed an excellent fit with the children with obesity data. Model 2 (TG: HDL-C ratio) of the first order constructs showed comparable model fitness indices Goodness of Fit (GFI), Akaike’s information criterion (AIC), and Bayes information criterion (BIC) with LAR. The least model fit was seen when using FBG as an IR surrogate. TG: HDL-C ratio performed better as IR surrogate in MetS structures (standardised factor loading = 0.39) compared to FBG (standardised factor loading = 0.27). Replacing FBG with TG: HDL-C ratio improved the MetS structure modelling in children with obesity. Furthermore, the model consisting of TG: HDL-C ratio was comparable with the reference model consisting of LAR. This study provides and extendsthe evidence for future use of TG: HDL-C ratio as an alternative for a primary clinical indicator to select children with obesity at a higher risk for MetS. Keywords: paediatric; obesity; metabolic syndrome; TG: HDL-C ratio; insulin resistance